S3N - Smart Solution for Substation Networks, an architecture for the management of communication networks in power substations (2018)
ABSTRACT: Today, the communications network has become an essential element to the operation of any type of organization or infrastructure, such is the case of the electrical power substations. Such networks in particular, demand high levels of availability and reliability, as the substation is a key element in the chain of energy generation and distribution. However, although recent network modernization introduced new features that allow optimizing the operation of the substation, the variety of devices present in such environment (Intelligent Electronic Devices (IEDs), Merging Units (MUs), Network Switches, IEEE 1588 Master Clock) and the huge set of application-level protocols (Sampled Measured Values (SV), Generic Object Oriented Substation Event (GOOSE), Manufacturing Message Specification protocol (MMS), Precision Time Protocol (PTP), among others), increase the management complexity. Nevertheless, in recent years, data networks have been permeated by two major trends aiming to facilitate the administration of complex networks: Software Defined Networking (SDN) and virtualizationtechnologies, which make the network management more flexible and enable the rapid development and deployment of network services. This thesis proposes a set of contributions to solve the research challenges around of the current operation of a power substation communication network that have not been tackled by the research community. To do that, it performs a comprehensive review of the appropriation of SDN as an enabler in the management and operation of the power substations communication networks. The first research challenge we identified in this work is that, to the best of our knowledge, there are not research works proposing a complete architecture for the management of the communications networks of the power substation; also existing works do not introduce the virtualization technologies as an enabler in this environment. They only present how the application of SDN concepts may improve the performance of different communication tasks in power substations. This thesis introduces a novel architecture called Smart Solution for Substation Networks (S3N), which presents a different way to represent the interaction among all elements involved in the operation of the power substation, taking the communications network as the central point and the SDN paradigm as a key element of its formulation. The second challenge found in this work is that there is no unique criterion to define the structure of the network topology since, in every power substation, the end user implements their own topologies or the topology suggested by a vendor. In this context, this thesis presents a methodology to specify and characterize a reliable topology that vii guarantees fault-tolerance, according to the guidelines described in the architecture S3N. In addition, this thesis presents alternative SDN solutions for loops-based topologies in the proposed network topology which would be technically unfeasible using common network protocols. These solutions include algorithms to solve problems related to the broadcast and multicast traffic management. Also, we discovered that, although the communication networks of modern electrical substations provide major benefits, various research articles have evidenced several vulnerabilities related to the operation protocols in this critical infrastructure. This thesis, in order to improve the security, presents two strategies to detect intrusions and one SDN approach to mitigate attacks in the reconnaissance phase. Finally, all these contributions would not be enough to guarantee a reliable operation without mechanisms to bring traffic differentiation and provisioning. This thesis makes the best out of the architecture proposed to deploy Quality of Service (QoS) inside power substation communication networks, under the SDN paradigm.